Creating Citizens : Liberal Arts, Civic Engagement, and the Land-Grant Tradition - Brunner, Brigitta R., 1971- (Book collections on Project MUSE., 2016)
"In Creating Citizens, professors and administrators at Auburn University's College of Liberal Arts recount valuable, first-hand experiences teaching Community and Civic Engagement (CCE). They demonstrate that, contrary to many expectations, CCE instruction both complements the mission of liberal arts curricula and powerfully advances the fundamental mission of American land-grand institutions. The nine essays in Creating Citizens offer structures for incorporating CCE initiatives into university programs, instructional methods and techniques, and numerous case studies and examples undertaken at Auburn University but applicable at any university. Many contributors describe their own rewarding experiences with CCE and emphasize the ways outreach efforts reinvigorate their teaching or research. Creating Citizens recounts the foundation of land-grant institutions by the Morrill Act of 1862. Their mission is to instruct in agriculture, military science, and mechanics, but these goals augmented rather than replaced an education in the classics, or liberal arts. Land-grant institutions, therefore, have a special calling to provide a broad spectrum of society with an education that not only enriched the personal lives of their students, but the communities they are a part of. Creating Citizens demonstrates the important opportunities CCE instruction represents to any university but are especially close to the heart of the mission of land-grant colleges. In open societies, the role and mission of public institutions of higher learning that are supported by public subsidies are perennial subjects of interest and debate. Creating Citizens provides valuable insights of interest to educators, education administrators, students, and policy makers involved in the field of higher education."--